2019
DOI: 10.1080/1828051x.2019.1615851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant extracts derived from thyme and chamomile on the growth performance, gut morphology and immune system of broilers fed aflatoxin B1 and ochratoxin A contaminated diets

Abstract: This study was conducted to evaluate the ability of chamomile flower extract (CFE) and thymeoil extract (TOE) for the preventing effect of ochratoxin A (OTA) and aflatoxin B 1 (AFB) in broiler productivity, biochemical parameters, gut morphology and immune response of broilers. The experiment was conducted as a 3 Â 4 factorial arrangement, being the factors: phytogenic additives (control, 3 g/kg diet of CFE, or 3 g/kg diet of TOE) and dietary contaminated diets (none, 0.50 mg/kg diet of AFB, 0.25 mg/kg diet of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The current study showed that HD was able to mitigate hepatotoxicity induced by AFB 1 in broilers. Birds that consumed AFB 1 diets exhibited a reduction in final body weight, body weight gain, feed intake, and gain/feed of broilers, all of which remain in agreement with previous studies [13,31,32]. This poor growth performance could be related to anorexia and inhibition of lipogenesis and protein synthesis [32,33].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study showed that HD was able to mitigate hepatotoxicity induced by AFB 1 in broilers. Birds that consumed AFB 1 diets exhibited a reduction in final body weight, body weight gain, feed intake, and gain/feed of broilers, all of which remain in agreement with previous studies [13,31,32]. This poor growth performance could be related to anorexia and inhibition of lipogenesis and protein synthesis [32,33].…”
Section: Discussionsupporting
confidence: 90%
“…Lately, the use of natural active biological compounds derived from plants has been attracting more attention. Some metabolites of herbs have been proven to be an effective alternative that can ameliorate the adverse effects of AFB 1 in broiler diets [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of saponins, phenolic compounds originated from soapnut ( Sapindus mukorossi ) at 150 mg/kg could improve the cell-mediated and humoral immune response of broilers without adverse effects on optimum body weight [ 87 ]. Inclusion of thyme essential oil at 3 g/kg could improve serum IgG, IgA, antibody titer against ND vaccine in broilers and could eliminate the adverse effects of ochratoxin A and aflatoxin B 1 in broiler diets [ 88 ]. In broilers challenged with LPS, dietary supplementation of carvacrol essential oils as phenolic compound at 200 μL/L could prevent the expression of inflammatory cytokines that ensured the anti-inflammatory role of carvacrol in broilers [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nazarizadeh et al [ 49 ] described a precision livestock farming system for a real time monitoring of animals’ health status in order to enhance the safety of the meat chain. The use of a low-cost multispectral sorter was used to select and remove the maize kernels which were contaminated by aflatoxins and fumonisins in Kenya (the machine was calibrated by building a mathematical model relating reflectance at nine distinct wavelengths (470–1550 nm) to mycotoxin levels of single kernels [ 50 ]).…”
Section: Systems For the Control Of Mycotoxins In Feed And Foodmentioning
confidence: 99%